CESifo World Economic Survey August 2009 - Gernot Nerb; Anna Stangl (CESifo World Economic Survey, 2009)
World Economic Climate: World Economic Climate improves - Economic Expectations: Economic expectations point to recovery - Inflation: Stabilization of price trend expected - Interest rates: Increase of long-term interest rates expected - Currencies: Euro appears overvalued - Special topic: Corruption and the financial crisis
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies; Corruption; financial crisis